1980
DOI: 10.1113/jphysiol.1980.sp013125
|View full text |Cite
|
Sign up to set email alerts
|

The time course of sodium inactivation in squid giant axons.

Abstract: SUMMARY1. The time course of Na inactivation was studied in intact and perfused squid giant axons under voltage-clamp conditions.2. The pulse programme consisted of a conditioning pulse of varying duration, followed after an interval of 3-8 msec by a test pulse. The measurements were done in sea water with 1/3 or 1/5 of the normal Na concentration. In most experiments a 100 ssec conditioning pulse was sufficient to reduce INa peak elicited by the test pulse. In some experiments even a 50,sec conditioning pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 20 publications
7
53
0
Order By: Relevance
“…In Ranvier nodes of Rana fibres two time constants were observed both in TEA-free solutions and in the TTX-sensitive current (J. Schmidtmayer & W. Ulbricht; personal communication). In the squid axon Gillespie & Meves (1980) did not find a second time constant in the time course of inactivation. Attwell, Bergman & Ojeda (1979) suggested that the slow process of current decay might be (at least partly) induced by accumulation of sodium ions at the inner side of the membrane during K.-D. KNIFFKI, D. SIEMEN AND W. VOGEL longer pulses.…”
Section: Double Exponential Decay Of Inactivationmentioning
confidence: 94%
See 1 more Smart Citation
“…In Ranvier nodes of Rana fibres two time constants were observed both in TEA-free solutions and in the TTX-sensitive current (J. Schmidtmayer & W. Ulbricht; personal communication). In the squid axon Gillespie & Meves (1980) did not find a second time constant in the time course of inactivation. Attwell, Bergman & Ojeda (1979) suggested that the slow process of current decay might be (at least partly) induced by accumulation of sodium ions at the inner side of the membrane during K.-D. KNIFFKI, D. SIEMEN AND W. VOGEL longer pulses.…”
Section: Double Exponential Decay Of Inactivationmentioning
confidence: 94%
“…In contrast, Chandler, Hodgkin & Meves (1965), Gillespie & Meves (1980) and Dodge (1963), performing two-pulse experiments on perfused squid giant axons and on nodes of Ranvier, respectively, did not detect a delayed onset of inactivation. In the latter preparation Chiu (1977) found a pronounced delay in the recovery from inactivation but did not observe a delay in the onset of the inactivation process.…”
Section: Introductionmentioning
confidence: 99%
“…In some cells there was evidence for a second exponential decline of long time constant as described by Shakhovalov (1977), whereas in others the currents appeared to reach a steady value with a single exponential (cf. Akaike et al 1978;Adams & Gage, 1979 (Gillespie & Meves, 1980 in control current size over the course of the experiment measurements were bracketed with controls (no prepulse) and current during the test pulse is expressed relative to that in the absence of a prepulse (V2/12(0)). Inward current during the test pulse declined exponentially with increasing prepulse duration with r = 58 msec, which is similar to values obtained at the same potential from the decline of inward currents.…”
Section: Ca Current Inactivationmentioning
confidence: 99%
“…Benzyl alcohol was obtained from Aldrich (gold label). The sodium concentration of the ASW was often reduced in order to decrease the sodium current and thus the voltage drop across the series resistance (see Gillespie & Meves, 1980). This was achieved by substituting the sodium ion with equimolar amounts of the tetramethyl ammonium ion (TMA+).…”
Section: Methodsmentioning
confidence: 99%
“…at which inactivation was complete was subtracted and the difference (IIpeak -Ioo) was plotted on a logarithmic scale against time. The points fall on a straight line from which the time constant of inactivation (Th) can be calculated (Gillespie & Meves, 1980). Benzyl alcohol normally caused a small reversible decrease in Th.…”
Section: Membrane Currents Under Voltage Clampmentioning
confidence: 99%